PROBLEMATIKA PEMBELAJARAN JARAK JAUH MATA PELAJARAN FIQIH DI SMA MUHAMMADIYAH 1 SURAKARTA - Helmi Setyoningsih; Nurul Latifatul Inayati; Zaenal Abidin (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2021)
The COVID-19 pandemic has resulted in unusual changes, especially in the world of education, which initially used the face-to-face method when the learning process was changed to distance learning (PJJ). Distance learning is learning that is limited by space and time between teachers and students. So it takes a communication tool to connect the two. When distance learning (PJJ) takes place, there are many problems faced by students and teachers, especially in fiqh lessons, so efforts / solutions are needed to deal with these problems. This study aims to describe the process of implementing distance learning, the problems faced by teachers, and the teacher's efforts to overcome the problems of distance learning in the class X Fiqh subject at SMA Muhammadiyah 1 Surakarta. This research is a type of qualitative research, so that in conducting data analysis using qualitative descriptive analysis methods. As for the data collection using interviews, documentation, and observation. The results of this study showed that 1) The process of implementing learning at SMA Muhammadiyah 1 Surakarta was carried out by Distance Learning (PJJ) before starting learning the teacher did planning, namely preparing lesson plans, smartphones, books and other media that would be used. In the implementation process, the teacher delivers material or assigns assignments via Google Classroom or Zoom. And finally, the teacher evaluation process gave a post-test via google form which was sent via google classroom. 2) The problems of distance learning in class X fiqh subjects at SMA Muhammadiyah 1 Surakarta Academic Year 2020/2021 are the teacher's lack of mastery of technology, not all students have smartphones, poor internet network, expensive quota fees, difficulty assessing student learning outcomes, students have difficulty understanding the material, learning motivation decreases and teachers find it difficult to control students during distance learning. 3) The teacher's efforts to overcome the problems of Distance Learning at SMA Muhammadiyah 1 Surakarta are holding google classroom training, students contact the teacher if they miss material, the teacher gives more time in collecting assignments, providing monthly subsidies and getting a free quota from the government, students can contact the teacher if there is material that they do not understand, and the teacher can establish communication with good parents to find out the child's development.